Vingtième siècle : la redécouverte de l’historicité du droit - Paolo Grossi (Clio@Themis)
Questioning the characteristics of modernity and post-modernity in law, this article examines the consequences that these characteristics may have had for the history of law. With the recognition of the social nature of the law, the consciousness of the historicity of law constitutes an essentiel conquest in the collective consciousness of the Europe of civil law.